Answer:
Need more info
Step-by-step explanation:
Answer:
![9x^2-5x-7](https://tex.z-dn.net/?f=9x%5E2-5x-7)
Step-by-step explanation:
![d(x)=9x^2\\g(x)=5x+7\\d(x)-g(x)=\\(9x^2)-(5x+7)=\\9x^2-5x-7](https://tex.z-dn.net/?f=d%28x%29%3D9x%5E2%5C%5Cg%28x%29%3D5x%2B7%5C%5Cd%28x%29-g%28x%29%3D%5C%5C%289x%5E2%29-%285x%2B7%29%3D%5C%5C9x%5E2-5x-7)
Hope this helps!
The correct answer is: [C]: " c(x) = –8x²<span> + 3x – 5 " .
_________________________________________________________
The quadratic function takes the form of:
_________________________________________________________
" f(x) = ax</span>² + bx + c " .
_________________________________________________________
Answer choice: [C]: " c(x) = –8x² + 3x – 5 " ;
is the only answer choice provided that takes that form of the quadratic function:
" f(x) = ax² + bx + c " :
in which: " a = -8 " ; " b = 3 " ; " c = -5 " .
____________________________________________________
Answer:
y=-2x^2-4
Step-by-step explanation:
The parabola is wider than it's parent function, y = x^2. Therefore the coefficient, of x^2 (when you refer to quadratic equations it's a) should be greater than 1. Let's take 2.
y = 2x^2
Now it is reflected across the x-axis, so the equation turns to y = -2x^2. The vertex is shifted down 4. Note that it is shifted down, along the y-axis. This makes 'c' (again quadratic equations) -4.
Final Equation: y=-2x^2-4
Answer:
210 in²
Step-by-step explanation:
6*2.5+6*6*2+(8+6)*2.5+10*2.5+1/2*6*8*2+6*2.5= 210 in²